La vita prima della fine Lo stato vegetativo tra etica, religione e diritto - Galletti, Matteo; ZULLO, SILVIA (Studi e saggi, 2008)
In recent decades the clinical condition of the permanent vegetative state has raised debates regarding the treatment of those patients who, as a result of brain damage, have irreversibly lost consciousness while biologically continuing to live. The media have also provided ample coverage of celebrated cases, such as those of Karen Quinlan, Anthony Bland, Terry Schiavo and Eluana Englaro. Behind these names are the stories of individuals, moral dilemmas that incite reflection and throw down challenges to the law. This book contains essays by experts in various disciplinary areas - philosophy, religion and law - and is designed to offer a contribution to the debate, so as to clarify which instruments can best protect human rights and dignity even in borderline clinical situations.